2022
DOI: 10.1007/s10904-022-02489-5
|View full text |Cite
|
Sign up to set email alerts
|

Two Cu(I\II) Coordination Polymers for Photocatalytic Degradation of Organic Dyes and Efficient Detection of Fe3+ Ions

Abstract: Two new copper-based coordination polymers (CPs), {[Cu I (H 2 PO 4 )(dpe)] 5 (dpe) 0.5 (H 2 O) 7 } n (Cu-dpe(I)) and {[Cu II (HPO 4 )(dpe)(H 2 O)](H 2 O) 3 } n (Cu-dpe(II)) (dpe = 1,2-di(4-pyridyl)ethylene), had been successfully constructed by hydrothermal method and ball milling method respectively. The crystal structures of two coordination polymers were determined by single crystal X-ray diffraction. The synthetic temperature caused their structure differences. The differences of structure and properties b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…In 2021, Zhu et al [73] successfully prepared a material (rGO@Fe 3 O 4 /Cu 2 O@ZnO) with strong hydrophobicity, high photocatalytic performance, and recyclability, and its photocatalytic degradation efficiency of acrylamide (AM) reached 97.3%. In addition to this, a large number of studies have reported the study of photocatalysts such as Cu 2 O [74,75], α-Fe 2 O 3 [76,77], Au [78], Ag [79], and Cu [80] for polymer degradation. Photocatalytic oxidation can utilize solar energy and save energy.…”
Section: Photocatalytic Oxidationmentioning
confidence: 99%
“…In 2021, Zhu et al [73] successfully prepared a material (rGO@Fe 3 O 4 /Cu 2 O@ZnO) with strong hydrophobicity, high photocatalytic performance, and recyclability, and its photocatalytic degradation efficiency of acrylamide (AM) reached 97.3%. In addition to this, a large number of studies have reported the study of photocatalysts such as Cu 2 O [74,75], α-Fe 2 O 3 [76,77], Au [78], Ag [79], and Cu [80] for polymer degradation. Photocatalytic oxidation can utilize solar energy and save energy.…”
Section: Photocatalytic Oxidationmentioning
confidence: 99%
“…The abundant presence of copper iodide metal clusters contributes to the semiconducting nature of the synthesized CPs. Recent studies have shown that while Cu­(I) CPs are effective in degrading dyes, they have the drawback of prolonged dye degradation time and low recyclability. , The applicability of CP1 and CP2 was also explored as photocatalysts for the degradation of methylene blue (MB) and rhodamine B (RHB) under sunlight. Our compounds show excellent photocatalytic efficiency with less time and high recyclability.…”
Section: Introductionmentioning
confidence: 99%